EXPLORING THE INFLUENCE OF LIFESTYLE BEHAVIOUR AND ACADEMIC EXPERIENCE OF UNDERGRADUATE STUDENTS IN KAZAKHSTANI UNIVERISTIES - Kenes, Aigerim (Nazarbayev University Graduate School of Education, 2025)
Lifestyle plays a pivotal role in the development of an individual’s life spheres, such as education, health, socialization, and career. This study focuses particularly on the influence of lifestyle behaviour on the academic experience of undergraduate students in Kazakhstan. The primary purpose of the study is to identify the direct and indirect factors that influence the academic experience of the students. Using an exploratory sequential mixed method, online surveys were conducted among 119 students, while semi-structured interviews were conducted with 10 students across two universities in Astana. The results of the study reveal that having a healthy lifestyle is important to maintain a good academic standing. It was found that students, who sleep enough, follow a nutritional diet with a high amount of fruit and vegetables, and do not smoke, tend to have better academic grades. In addition to these habits, regular physical activities and socialization have a positive influence on concentration, lecture attendance, and engagement. Whereas, lack of sleep, poor diet, drinking alcohol, smoking, and excessive technology use increase distraction level, and lead to worse academic performance. On the other hand, it was also discovered that drinking alcohol once or twice a month can be a positive predictor of good GPA, as part of socialization activities. This can be connected with the positive cultural acceptance of alcohol consumption. Based on the main results, the study highlights how crucial it is for higher education institutions to support healthy lifestyle choices to improve student academic achievement.
Keywords: lifestyle behaviour; healthy habits; Health Lifestyle Theory; academic experience; undergraduate students.; Type of access: Open